Mitochondrial respiration in B lymphocytes is essential for humoral immunity by controlling the flux of the TCA cycle - Urbanczyk, Sophia; Baris, Olivier R.; Hofmann, Jörg; Taudte, Verena; Guegen, Naïg; Golombek, Florian; Castiglione, Kathrin; Meng, Xianyi; Bozec, Aline; Thomas, Jana; Weckwerth, Leonie; Mougiakakos, Dimitrios; et al. (Cell Reports, 2022)
To elucidate the function of oxidative phosphorylation (OxPhos) during B cell differentiation, we employ CD23Cre-driven expression of the dominant-negative K320E mutant of the mitochondrial helicase Twinkle (DNT). DNT-expression depletes mitochondrial DNA during B cell maturation, reduces the abundance of respiratory chain protein subunits encoded by mitochondrial DNA, and, consequently, respiratory chain super-complexes in activated B cells. Whereas B cell development in DNT mice is normal, B cell proliferation, germinal centers, class switch to IgG, plasma cell maturation, and T cell-dependent as well as T cell-independent humoral immunity are diminished. DNT expression dampens OxPhos but increases glycolysis in lipopolysaccharide and B cell receptor-activated cells. Lipopolysaccharide-activated DNT-B cells exhibit altered metabolites of glycolysis, the pentose phosphate pathway, and the tricarboxylic acid cycle and a lower amount of phosphatidic acid. Consequently, mTORC1 activity and BLIMP1 induction are curtailed, whereas HIF1α is stabilized. Hence, mitochondrial DNA controls the metabolism of activated B cells via OxPhos to foster humoral immunity.
CRIS-Team Scopus Importer:2022-06-17
Keywords: B lymphocyte; class switch recombination; CP: Immunology; germinal center; HIF1; hypoxia inducible factor 1; mammalian target of Rapamycin; mitochondrial DNA; mitochondrial respiration; mTOR; oxidative phosphorylation; phosphatidic acid; plasma cell; TCA cycle